Influence of pH on CeIV-[AsIIIW9O33]9− association for the formation of hexanuclear cerium(iv) oxo-hydroxo-clusters stabilized by trivacant polyanions. Issue 2 (13th December 2019) - Dufaye, Maxime; Duval, Sylvain; Stoclet, Gregory; Loiseau, Thierry
Abstract : Influence of pH on Ce IV -AsW9 O33 association leads to the formation of four crystalline compounds incorporating classical and distorted hexanuclear cerium clusters. Abstract : Four hetero-polyoxometalate compounds were obtained in aqueous solutions, following the synthetic combination of Na9 [B-α-As III W9 O33 ] with the 4f tetravalent cerium cation in the presence of the formate ligand at different pH values (ranging from 1.5 to 6). All four molecules [Ce6 (μ 3 -O)4 (μ 3 -OH)4 (HCOO)3, 5 4 (As III W9 O33 )4 ] 2− compound 1, [(Ce6 (μ 3 -O)4 (μ 3 -OH)4 )(H2 O)4 (As III W9 O33 )(HCOO)9 ] 6− compound 2, [(Ce6 (μ 4 -O)3 (μ 3 -O)5 (μ 2 -H2 O)3 )(HCOO)3 (As V W9 O34 )3 ] 22− compound 3, and [(W4 O10 )(Ce6 (μ 3 -O)5 (μ 4 -O)3 (μ 2 -H2 O))(As V W9 O34 )3 2 ] 44− compound 4 were constructed around one to four hexanuclear cerium clusters of [Ce6 O8 ] type. For the compounds 1–3, the arsenato-polytungstate POM units and formate ligands were associated and participated in the stabilization of one cerium(iv )-bearing hexanuclear unit in a cyclic motif (1 ), a monomeric POM species for 2, and a trimeric POM species for 3 . However, in the last molecular system (4 ), only inorganic entities were bonded to the hexameric cerium(iv ) clusters. From the structural point of view, compound 4 appeared as the association of two compound 3 entities, in which the formate ligands were replaced by an inorganic tungsten-based sub-unit coming from the partial decomposition of the As III W9 O33 precursor. The behavior and the association modes of the four molecular species were explained on the basis of the pH variation used in their syntheses. All four compounds were characterized by single-crystal X-ray diffraction, IR spectroscopy, TGA, SEM/EDX microscopy, and ICP analyses. The solution behavior was assessed on compound 3 by using small angle X-ray scattering (SAXS) measurements.